A preliminary screening study with dermal tea formulations against 311 NM ultraviolet B radiation - (:unkn) unknown (My University, 2022)
One potential health benefit of Camellia sinensis extracts on the skin is protection from the detrimental effects of UV radiation. Tea polyphenols both absorb the UV and also alleviate the UV-induced damage in human skin. In this study, we aimed to test the protection of black and green tea gels against UV. The gels were prepared using a carbomer resin and freeze-dried black or green tea extracts. In formulations, total phenolic content, antioxidant activity, and free radical scavenging activity were tested. The sites were irradiated with an artificial narrow band UVB source 30 min after topical application of the formulations on separate regions of the upper back of 21 subjects, Black and green tea gels, and the commercial sunscreen protected the skin of volunteers against the UV erythema. Caffeine gel and carbopol control gels did not provide any protection. Commercial sunscreens can only protect the skin by absorbing or scattering UV radiation. However, tea extracts both absorb the UV radiation and also have the potential to repair the UV damage inside the skin due to their strong antioxidant contents. Tea extracts are safe for humans as well as for aqueous environments without toxicological concerns.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Dermatoloji; Kimya; Diğer; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Dermatology; Chemistry; Other; Natural Sciences; KİMYA, UYGULAMALI; Temel Bilimler (SCI); DERMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); DERMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Physical Sciences